Pengaruh Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Melalui Motivasi Di Rumah Sakit “Yakksi” Gemolong Sragen - Hartati Dyah Wahyuningsih -STMIK AUB Surakarta (Universitas Bina Sarana Informatika, 2015)
Abstract - The development of the hospital now very rapidly and attracted the attention of researchers to carry out research studies, particularly on the performance pegawainya.Penelitian who took the title Influence of leadership and organizational culture on employee performance through motivation in the Hospital